Acute mesenteric ischemia following lancehead snakebite: an unusual case report in the Northernmost Brazilian Amazon - Galan, Luis E. B.; Silva, Vitória Souza; Silva, Vitória Santos; Monte, Rommel C.; Jati, Sewbert R.; Oliveira, Isadora S.; Cerni, Felipe A.; Monteiro, Wuelton M.; Sachett, Jacqueline; Dantas, Domingos S. M.; Carbonell, Roberto C. C.; Pucca, Manuela B. (Frontiers in Medicine, 2023)
Snakebites have a great impact in the Brazilian Amazon, being the lancehead Bothrops atrox the species responsible for most accidents, disabilities, and deaths. This study shows a case report of an indigenous patient from the Yanomami ethnicity, male, 33 years-old, envenomed by a B. atrox snake. Envenoming caused by B. atrox are characterized by local manifestations (e.g., pain and edema) and systemic manifestations, mainly coagulation disorders. The indigenous victim was admitted in the main hospital of Roraima and evolved with an unusual complication, an ischemia and necrosis of the proximal ileum, requiring segmental enterectomy with posterior side-to-side anastomosis. The victim was discharge after 27 days of hospitalization with no complaints. Snakebite envenomations may evolve with life-threatening complications, which can be treated by the antivenom following access to a healthcare unit, often late in indigenous population. This clinical case shows the need of strategies that aim improvement in the access to the healthcare by indigenous people, as well as demonstrates an unusual complication that may result from lancehead snakebites. The article also discusses the decentralization of snakebites clinical management to indigenous community healthcare centers to mitigate complications.